Comparative study on the distribution of Pacinian corpuscles in the pancreas - Yang, Ting; Ren, Ke; Chen, Xiangquan; Toriumi, Taku; Li, Rujia; Li, Jun; Tokita, Konosuke; Yi, Shuang-Qin (Frontiers in Neuroanatomy, 2025)
BackgroundPacinian corpuscles (PCs) are pressure- and vibration-sensitive mechanoreceptors found in hairless skin, external genitalia, joints, ligaments, lymph nodes, prostate, bladder, etc. While they are documented in the pancreas of cats, their presence in the normal pancreas remains speculative.PurposeThe present study therefore investigated the distribution of PCs in the normal human pancreas and compared the findings with those in several other animal species.MethodsThe study subjects included 74 human cadaver specimens, 3 Cynictis penicillata, 2 Saguinus mystaxs, 1 Felis domesticus, and 10 Suncus murinus. Pancreatic tissues were prepared as paraffin sections for histological and immunohistochemical analyses of the main constituents of PCs (central axon, inner core, and outer core capsule).ResultsPCs were found in the pancreas of five human cadavers (7%), as well as in one C. penicillata, one S. mystax and one F. domesticus but not in S. murinus. The PCs varied in size, with the largest in the human pancreas measuring up to 1,106 μm—far exceeding those in animal pancreata, but less numerous than those in animals. Morphologically, animal PCs were mainly typical oval shapes, whereas PCs in the human pancreas were mostly irregular in shape. In addition, we found that PCs in animals and human pancreata had similar structures, with consistent expression of protein gene product 9.5, in axonic profiles, and diffuse vimentin immunoreactivity in the inner core, outer core, and capsule.ConclusionThis study confirmed the presence of PCs in a small number of healthy humans and some animal pancreata. The number, distribution characteristics, and morphology of PCs in the pancreata of animals and humans are quite different; however, their structures and immunohistochemical profiles are similar. The presence of PCs in the normal human pancreas is also a mystery, and the physiological role of PCs in the human pancreas requires further clarification.